The Role of Human Resource Practices in Improving Employee Efficiency A Field Study at Tishreen University"" - البهلول, ذوالفقار; حنان تركمان,; لينا فياض , (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to study the relationship between human resource practices on the one hand, and between the efficiency of employees at Tishreen University on the other hand, since the researcher relied on two dimensions of human resource practices represented by (selection and appointment, training), and the efficiency of employees as one of the dimensions of organizational performance. The researcher relied on the questionnaire as a tool for collecting primary data, as it was distributed to a sample of employees at Tishreen University (490) questionnaires, (412) were retrieved, valid for analysis (380) questionnaires, and to test the relationship between the variables of the study, the researcher used the T-test Student for one sample, as well as Pearson's correlation coefficient. Through the study, the research found a low level of selection and appointment, as well as a low level of training at the university, in addition to a low level of competence among employees at Tishreen University. The research also found a significant relationship between human resource practices (selection and appointment, training) and the efficiency of employees. Thus, there is a role for human resource practices in improving the efficiency of employees at Tishreen University. The research concluded with a set of recommendations and proposals related to the need to develop selection and appointment procedures, and the need to improve the process of identifying training needs in the university, in addition to improving the efficiency of employees by setting standards that ensure obtaining the required quality of employees; and other recommendations that would contribute positively to the effective role of human resources practices in improving the efficiency of employees.